2019
DOI: 10.3390/ani9100731
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Infusions of Glycerol Versus Propylene Glycol for the Regulation of Negative Energy Balance in Sheep: A Randomized Trial

Abstract: Simple SummaryPropylene glycol (PG) and glycerol are common energy substances used to supplement the feed of transitioning ruminants in order to minimize the development of metabolic disorders related to energy deficiency. Their effects on the energetic status of the animal have been, thus far, studied mostly by oral administration, which exposes them to substantial microbial metabolism in the rumen. This study compared the direct metabolic effects of these substances following their intravenous (IV) infusion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
(57 reference statements)
0
23
0
Order By: Relevance
“…In previous studies with sheep 16 , we found that feeding growing lambs a carbohydrates-rich grain-concentrate ration induces substantial hyperglycemia, with ~ 40% higher blood glucose levels than in lambs raised on a hay-based ration. Based on this observation and on the fact that sheep, as humans, are willing to overeat, we hypothesized that feeding them with that hyperglycemia-stimulating diet for an extended period will induce hepatic steatosis.…”
mentioning
confidence: 74%
“…In previous studies with sheep 16 , we found that feeding growing lambs a carbohydrates-rich grain-concentrate ration induces substantial hyperglycemia, with ~ 40% higher blood glucose levels than in lambs raised on a hay-based ration. Based on this observation and on the fact that sheep, as humans, are willing to overeat, we hypothesized that feeding them with that hyperglycemia-stimulating diet for an extended period will induce hepatic steatosis.…”
mentioning
confidence: 74%
“…Additionally, Piantoni and Allen [9] concluded that dosing 300 mL of PG to the cranial reticulo-rumen is more effective for ketosis treatment than dosing the double quantity of G due to the extensive metabolism of G by ruminal microbes to metabolites that are not glucogenic and added that adding G to the recommended dose of PG is doubtful to provide additional benefit. Intravenous administration of glycerol and PG effectively reduced hyperketonemia and lipolysis [32].…”
Section: Discussionmentioning
confidence: 95%
“…As a result, PG and G have different pathways to be metabolized into glucose. Therefore, their mixture in GPG250 is beneficial for hepatic synthesis of glucose [32,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mobilization increases initially non-esterified fatty acids in the liver that by its turn is partially transformed in ketone bodies, mainly β-hydroxybutyrate acid (BHB), but also acetoacetate and acetone (Radostits et al, 2007). The BHB may also become elevated in the bloodstream due to mobilization of the body's reserves, especially when there is a negative energy balance in lean pregnant ewes (Radostits et al, 2007;Kalyesubula et al, 2019). Blood ketosis can also evolve to a nervous condition (nervous ketosis) caused by a BHB-derived product, the isopropanol (Araújo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%